Identification of Possible Inhibitor Molecule against NS5 MTase and RdRp Protein of Dengue Virus in Saudi Arabia - Alwabli, Afaf S.; Qadri, Ishtiaq (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Non-structural protein 5 (NS5) is considered as an important protein in Dengue viruses (DENVs). It contains N-terminal methyltransferase (MTase) and C-terminal RNA-dependent RNA polymerase (RdRp) domains. NS5 plays a crucial role in the replication of Dengue viruses. Therefore it is considered as an attractive candidate for the development of therapeutics in anti-viral infections and diseases. Aim: The aim of proposed in-silico study was to to screen and identify potential lead molecules with drug like properties to inhibit the activity of NS5 protein in Dengue virus infections. Materials and Methods: Computational bioinformatics analysis was implemented to identify the lead molecules with inhibition activity against MTase and RdRp domains of Dengue virus protein NS5. Phytochemicals and active bioassay compounds were screened based on their reported antiviral mactivities. A total of fifty-one natural compounds and one hundred active compounds were selected by evaluating eighty one bioassay studies. Results: Results of the current study revealed galactomannan, galactan, hyperside, carrageenan, tetrahydroxy, lamdacarragenon, zosteric acid, trihydroxy, quercetin and sulfoximine as top inhibitors of the Dengue virus NS5 protein. Lead molecules namely lamdacarragenon, carrageenan, balsacanea, galactan, trihydroxy, hyperside, myricetin, glycyrrhiza, isosilandrin, rhodiola and silyhermin showed the utmost hydrogen bonding. Overall, we observed that the bioassay active compounds showed less interaction with the MTase and RdRp domains of NS5 protein as compared to natural ligands. Conclusion: Based on the findings of current study, we concluded that the phytochemicals are the most favourable among the docked molecules that showed a significant inhibitory activity against the MTase and RdRp domains of NS5 protein of dengue viruses. We suggest that these lead molecules can be validated experimentally and implemented for the development of therapeutics in viral infections like Dengue.
Keywords: Dengue virus; Molecular docking; Molecular structure; MTase; NS5; Non-structural viral proteins; RdRp